Fluid Dynamic Gauging for Studying Early Stages of Swelling of Fouling Deposits. Issue 15 (8th September 2022) - Tsai, Jheng-Han; Cuckston, Georgina; Schnöing, Lukas; Augustin, Wolfgang; Scholl, Stephan; Hallmark, Bart; Wilson, Ian
Abstract: A new variant of the fluid dynamic gauging technique for determining the thickness of soft fouling layers in situ and in real time is reported. The sideways fluid dynamic gauging (SiDG) device allows measurements to be made shortly after a deposit layer contacts a solution, allowing processes such as swelling to be characterized accurately. Two applications of the device are reported: ( i ) in cleaning, monitoring the change of thickness of a complex food soil when it is contacted with aqueous solutions at different temperatures, pH and surfactant content, and ( ii ) in fouling, in determining the thickness, thermal conductivity and strength of deposits generated from whey protein solutions on heated stainless steel substrates. The evolution of fouling resistance for the whey protein deposits indicates that significant aging takes place during the fouling test, which is confirmed by changes in the thermal properties and strength of the deposit layer as measured by the SiDG device.